Applications in Light-induced Spectroscopy with violet LED lamp: Autofluorecence - Etcheverry, María Eugenia (2023)
The main objective of the present study was to develop a violet LED light source suitable for medical application devoted to the diagnostic and treatment of non-melanoma skin cancers. For this propose, we constructed a 12 W violet LED lamp (with maximum emission peak at 405 nm) made up of four mobile 3 W LED. The LED lamp was characterized employing a spectrometer coupled to an optical fiber. The irradiance, the radiant power and the radiant intensity for different distances between the lamp and the detector was assessed. Data were compared with a simulated LED lamp by using the Zemax optic software for the realization of luminaries with the desired characteristics as required for medical applications.The developed lamp in combination with a portable spectrometer was employed under medical supervision to detect differences in the emission spectrum of skin suspicious regions and healthy ones of a patient with non-melanoma skin cancer. The light of the LED lamp was concentrated in the examined region by means of the proper focusing of the four individual LEDs, rendering a high intensity homogeneous spot. Thus, endogenous chromophores at the skin were excited, and the emission intensity appeared to be enough to detect an enhanced peaked structure around 600 nm for some suspicious regions before treatment, and that were absence in healthy regions. These differences can be related to the augmented protoporphyrin IX content in neoplastic regions. Results presented in this work indicates the usefulness of the developed LED lamp as an easy-to-use device for the non-invasive detection of skin neoplastic pathologies, before and after treatment, with the aim of better define the malignant regions as well as predict the outcome of a certain treatment.